Low rates of headache and migraine associated with intravenous immunoglobulin infusion using a 15-minute rate escalation protocol in 123 patients with primary immunodeficiency - Geng, Bob; Clark, Kim; Evangelista, Mark; Wolford, Eric (Frontiers in Immunology, 2023)
Headache and migraine adverse events are common concerns in the administration of intravenous immune globulins (IVIG). Trials of IVIG for primary immunodeficiency (PI) are typically small and have reported headache and migraine data inconsistently. We analyzed headache and migraine in pooled data from three pivotal trials of Gammaplex® 5% and 10% in PI (NCT00278954 from January 18, 2006; NCT01289847 from January 27, 2011; NCT01963143 from September 13, 2013). The trials were pooled in a retrospective analysis that included two 12-month open-label non-comparative trials of the 5% IVIG product and one 6-month open-label crossover bioequivalence trial comparing the 5% IVIG and 10% IVIG products. The population included adult and pediatric patients, who received IVIG infusions of 300-800 mg/kg/infusion every 21 or 28 days using a 15-minute rate escalation protocol. In total, 1482 infusions were administered to 123 patients, with 94.6% of infusions achieving the maximum infusion rate. At least one product-related headache was reported in 6.1% (90/1482) of infusions. At least one product-related migraine was reported in 0.5% (7/1482) of infusions. Headache rates were higher for adults vs pediatric patients, females vs males, and 21-day vs 28-day dosing schedules, but were similar for the 5% and 10% IVIG products. Most headaches and migraines occurred during or within 72 hours of the infusion. Rates decreased after the first few infusions. Patients receiving this IVIG product on a 15-minute rate escalation protocol had low rates of headache and migraine for both the 5% and 10% formulations.